Prototipo de retroalimentación auditiva para la rehabilitación de marcha en enfermedad de Parkinson (2017)
Abstract: Parkinson's disease (PD) is a degenerative disorder, affecting the 1% of the population older than 65. It is characterized by deterioration of the motor automaticity given by the basal ganglia, resulting in clinical manifestations such as bradykinesia, hypokinesia, altered postural balance and gait. In addition, PD affects the ability to learn new motor tasks over the long-term. In this way, people affected with PD depend on the attentional system and cognitive control to execute movements that have already been learned and are usually automated. Given the progressive nature of disease and the limitations of surgical and pharmacological treatments, motor rehabilitation strategies play a role in maintaining the level of functional independence. Favorable recommendations have been found in the literature regarding the use of external auditory cues to facilitate the execution of the gait pattern because they supplement the motor automaticity impairment. However, there is still some question as to how to provide such auditory moduli to optimize motor response effects in terms of synchronization, automaticity and magnitude of change in gait variables. There is a hypothesis that linearity in the motor response enhance motor automaticity and motor learning. In the present work an auditory feedback prototype was developed by means of a semi-automatic strategy of gait characteristics quantification, to study both the temporal synchronization and the linearity between the rate of Auditory stimulation and the spatiotemporal response of the group of people with Parkinson's disease (n = 12) and control subjects (n = 7). For this purpose, a protocol of auditory stimulation with a set o variables related with high and low modulation of cadence was designed based on the existing literature. It was found that the best temporal synchronization are in the order of 110-120 bpm in high cadence and 80-100 bpm in low cadence. A strong linear correlation (R 0.9) was observed between the stimuli (auditory input) and the motor response in cadence and speed (motor output) in the majority of participants. However, the response in terms of step length showed a lower linear correlation and greater variability (0;21 R 0;9). Regarding the magnitude of the change achieved, a great variation was observed from baseline in cadence (28-43 %) and walking speed, especially in subjects of PD stage 3 (28-76 %). On the other hand, we did not observe the expected increase in step length with decreasing cadence. Therefore, the synchronization of the stimuli (auditory input) and the motor response (output motor), as its linear or nonlinear character of the same, and the effective modulation of the spatio-temporal variables Of the gait, can be used as descriptors of automatism and the initial phase of motor learning in the immediate term, called acquisition. The implementation of a closed-loop system will provide the tool to optimize the motor response according to these criteria.